Fatal cardiac thromboembolism in a patient with a pacemaker during ureteroscopic lithotripsy for ureter stone: a case report - Mee Young Chung; Su Min Chae; Chang Jae Kim (Korean Journal of Anesthesiology, 2015)
Intracardiac thrombosis is an infrequent and fatal complication in patients with an inserted pacemaker. A patient with an inserted pacemaker scheduled for ureter stone removal experienced cardiac arrest and cardiopulmonary resuscitation under general anesthesia. Echocardiography showed multiple intracardiac thrombi. Preoperative diagnostic workup including echocardiography for the detection of pacemaker lead thrombus, and the need for anticoagulation should be considered in patients with an inserted pacemaker and high-risk factors for thrombosis.